Ordinance no. 29, An Ordinance to Preserve the Public Peace, § 1, YPSILANTI, REVISED CHARTER OF THE CITY (Ypsilantian Publishing House 1898) (Approved 1882). - (:unkn) unknown (General Publisher, 1882)
Prohibited the concealed carry of firearms, dirks and other deadly weapons
--
Keywords: CARRY - CONCEALED